The study of prevalence of metabolic syndrome in the first degree relatives of type 2 diabetes mellitus patients - Mittal, Mahim; Gupta, Himanshu; ., Deepshikha (International Journal of Research in Medical Sciences, 2018)
Background: Metabolic syndrome (MetS) is associated with higher incidence of new onset DM. First degree relatives (FDR) of T2DM patients also have an increased risk of new onset DM due to common genetic factors that can lead to obesity and dyslipidemia. Objectives of research work was to study the prevalence of MetS in FDR of T2DM patients. Methods: Cross-sectional study of FDR of T2DM patients. MetS defined by both IDF and NCEP-ATPIII criteria. All subjects underwent necessary biochemical tests, a detailed history in a pre defined proforma was taken and clinical examination was done as per protocol. Results: Mean age was 43.61±11.7 years. Prevalence of MetS was 35% by IDF and 25% by NCEP-ATPIII. According to IDF criteria, the most prevalent risk factors among FDR were central obesity and hypertension. Prevalence of MetS was higher in urban, sedentary and obese population. Conclusions: Prevalence of MetS is more in FDR of T2DM than that reported in the general population. Central obesity is the most prevalent risk factor. Targeted lifestyle intervention in this population may help prevent the development of MetS and T2DM.